Massachusetts' Parental Consent Law and Procedural Timing Among Adolescents Undergoing Abortion. Issue 5 (May 2019) - Janiak, Elizabeth; Fulcher, Isabel R.; Cottrill, Alischer A.; Tantoco, Nicole; Mason, Ashley H.; Fortin, Jennifer; Sabino, Jamie; Goldberg, Alisa B.
Abstract : OBJECTIVE: To describe individual-level delay in obtaining abortion associated with use of the Massachusetts judicial bypass system, which legal minors (aged 17 years or younger) use to obtain abortion without consent of a parent or legal guardian in the setting of Massachusetts' parental consent law for abortion. METHODS: We conducted a retrospective cohort study of 2, 026 abortions among minors at a large, statewide network of abortion clinics between 2010 and 2016. Delay was defined as the number of calendar days between the minor's first call to the clinic to schedule an abortion, and the day the abortion was received. RESULTS: In the study population, 1, 559 (77%) abortions were obtained with parental consent and 467 (23%) using judicial bypass. Abortions after judicial bypass were more common among minors identifying as Hispanic, non-Hispanic black, or other race, those of low socioeconomic status (as indicated by having Medicaid insurance) and those with a prior birth or prior abortion (all P <.05). Minors with parental consent received their abortion a mean of 8.6 days after initial contact, compared with 14.8 days for minors with judicial bypass, for an unadjusted difference of 6.1 days. In multivariable linear regression modeling adjusting for demographic differences between groups, this difference persisted: minors who obtained abortions after judicial bypass had a significantly greater delay compared with those with parental consent (adjusted mean difference = 5.2 days; 95% CI 4.3 to 6.2). Using multivariable logistic regression modeling, minors with judicial bypass also had higher odds of becoming ineligible for medication abortion between the day of first call and the day of procedure (adjusted odds ratio 1.57; 95% CI 1.09 to 2.26). CONCLUSION: Massachusetts' parental consent law for abortion is associated with delay among minors and thereby may constrain the clinical options available to them. Abstract : Massachusetts' abortion parental consent law is associated with clinically significant delays, which may constrain options available for the clinical management of minors undergoing abortion.